Genetic relatedness of Plasmodium falciparum isolates and the origin of allelic diversity at the merozoite surface protein-1 (MSP-1) locus in Brazil and Vietnam - Hoffmann, Erika H.E.; Ribolla, Paulo E.M. [UNESP]; Ferreira, Marcelo U. (Springer Nature, 2003)
Background: Despite the extensive polymorphism at the merozoite surface protein-1 (MSP-1) locus of Plasmodium falciparum, that encodes a major repetitive malaria vaccine candidate antigen, identical and nearly identical alleles frequently occur in sympatric parasites. Here we used microsatellite haplotyping to estimate the genetic distance between isolates carrying identical and nearly identical MSP-1 alleles. Methods: We analyzed 28 isolates from hypoendemic areas in north-western Brazil, collected between 1985 and 1998, and 23 isolates obtained in mesoendemic southern Vietnam in 1996. MSP-1 alleles were characterized by combining PCR typing with allele-specific primers and partial DNA sequencing. The following single-copy microsatellite markers were typed: Polyα, TA42 (only for Brazilian samples), TA81, TA1, TA87, TA109 (only for Brazilian samples), 2490, ARAII, PfG377, PfPK2, and TA60. Results: The low pair-wise average genetic distance between microsatellite haplotypes of isolates sharing identical MSP-1 alleles indicates that epidemic propagation of discrete parasite clones originated most identical MSP-1 alleles in parasite populations from Brazil and Vietnam. At least one epidemic clone propagating in Brazil remained relatively unchanged over more than one decade. Moreover, we found no evidence that rearrangements of MSP-1 repeats, putatively created by mitotic recombination events, generated new alleles within clonal lineages of parasites in either country. Conclusion: Identical MSP-1 alleles originated from co-ancestry in both populations, whereas nearly identical MSP-1 alleles have probably appeared independently in unrelated parasite lineages.
Keywords: merozoite surface protein 1; allele; bacterium isolation; Brazil; clone; correlation analysis; DNA sequence; gene identification; gene locus; gene rearrangement; genetic distance; genetic variability; haplotype; heterozygosity; human; major clinical study; microsatellite marker; mitotic recombination; molecular phylogeny; nonhuman; Plasmodium falciparum; polymerase chain reaction; Viet Nam